2018
DOI: 10.1093/nar/gky661
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated mutations of histones H2B, H3.1 and H2A.Z.1 affect the structure and stability of the nucleosome

Abstract: Mutations of the Glu76 residue of canonical histone H2B are frequently found in cancer cells. However, it is quite mysterious how a single amino acid substitution in one of the multiple H2B genes affects cell fate. Here we found that the H2B E76K mutation, in which Glu76 is replaced by Lys (E76K), distorted the interface between H2B and H4 in the nucleosome, as revealed by the crystal structure and induced nucleosome instability in vivo and in vitro. Exogenous production of the H2B E76K mutant robustly enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 44 publications
7
90
0
Order By: Relevance
“…All samples were tested using the Nu.Q TM H3.1 assay. This is an enzyme-linked immunosorbent assay (ELISA) with a capture antibody directed at histone 3.1 and nucleosome specific detection antibody (18). Assays were performed according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were tested using the Nu.Q TM H3.1 assay. This is an enzyme-linked immunosorbent assay (ELISA) with a capture antibody directed at histone 3.1 and nucleosome specific detection antibody (18). Assays were performed according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to histone H3, two recent reports revealed another class of oncogenic mutation in histone H2B. 7,8 The glutamic acid at position 76 of H2B was found to be replaced by lysine in multiple cancers, including breast and lung carcinomas. Cells expressing the H2BE76K mutation acquired oncogenic phenotypes as a result of aberrant gene expression associated with cancer pathways, an effect possibly due to the destabilization of the histone octamer by H2BE76K.…”
Section: Dear Editormentioning
confidence: 99%
“…Several of these genes are associated with tumour initiation and progression but not well documented at the field of melanoma, however, according to the results of this present study, they might have roles in BRAFi resistance. cBioPortal for Cancer Genomics database supports the idea that seventeen canonical histone H2B genes including HIST1H2B, HIST1H2BM has been found to be involved in cancer progression [44], however no direct role of the genes are described yet. Kim et al reported that CENPF is functionally involved in the tumorigenesis of human cancers and cancer driver genes [52].…”
Section: Discussionmentioning
confidence: 97%
“…Based on the published data approximately 80% of melanoma cell lines show overexpressed DDAH-1 that represent a potential target for control of nitric oxide production in melanoma cell line [43]. On the other hand suppression of S-phase histone HIST1H2BB can improve treatment outcome in melanoma cells [44]. In contrast, genes that were commonly downregulated in sensitive and resistant melanoma spheroids, including MMP16, IGF1R and FLOT1, are associated with malignancy, and several studies have reported that these genes are related to the aggressive behaviour of melanoma [45,46].…”
Section: Discussionmentioning
confidence: 99%